Ideal body weight-based determination of minimum oral calories beneficial to function and survival in ALS - Nakamura, Ryutaro; Kurihara, Mika; Kobashi, Shuhei; Tamaki, Yoshitaka; Ogawa, Nobuhiro; Kitamura, Akihiro; Yamakawa, Isamu; Bamba, Shigeki; Terashima, Tomoya; Urushitani, Makoto (Frontiers in Neurology, 2023)
This study sought to identify the optimal caloric intake to improve function and survival in ALS patients by comparing oral intake per ideal body weight (IBW) and its discrepancy with total energy expenditure (TEE) using the Shimizu formula. A retrospective analysis of 104 ALS patients was conducted, categorizing them based on their average intake during the first week after admission using two primary intake cutoffs: 25kcal/kgIBW and 30kcal/kgIBW. The variance between oral intake and TEE was also evaluated using -300 kcal and 0 kcal as reference points. Results showed a significant negative correlation between oral caloric intake per IBW and functional decline rate (rs = -0.35, p < 0.001), but the variance from TEE was not significantly correlated (-0.11, p = 0.27). Survival data showed that patients consuming less than 25kcal/kgIBW had a median survival of 24 months, increasing to 38 months for those consuming between 25-30kcal/kgIBW and 63 months for those consuming 30kcal/kgIBW or more. Deviations from the TEE did not significantly affect survival (p = 0.36). Among patients consuming less than their TEE, those consuming less than 25kcal/kgIBW had a shorter median survival (24 months) compared to their counterparts (46 months) (p = 0.022). Consumption of less than 25 kcal/kgBW emerged as a significant negative predictor of patient outcome, independent of factors such as age, gender or disease progression. In conclusion, intakes of 25 kcal/kgIBW or more are correlated with improved ALS outcomes, and larger, multi-regional studies are recommended for deeper insights.